2022
DOI: 10.1186/s12884-022-04544-y
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude and associated factors of childbirth fear among pregnant women attending antenatal care at public hospitals in Ethiopia: a cross-sectional study

Abstract: Background Childbirth fear affects 5–40% of all mothers around the world, and there is mounting evidence that it has harmful impacts on women’s health. It could potentially lead pregnant women to feel isolated and unsupported if not identified. But studies addressing this issue are limited in Ethiopia. Therefore, this study was aimed at assessing the magnitude and associated factors of childbirth fear among pregnant women attending antenatal care at public hospitals in West Wollega Zone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…Labor pain is a normal process that pregnant women experience during labor. Between 5% and 40% of all mothers worldwide experience significant fear of childbirth (FOC) 1,2 . Numerous studies indicate that this fear is often a major reason for requests for cesarean delivery 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Labor pain is a normal process that pregnant women experience during labor. Between 5% and 40% of all mothers worldwide experience significant fear of childbirth (FOC) 1,2 . Numerous studies indicate that this fear is often a major reason for requests for cesarean delivery 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Giving birth in a health facility is safe since the attendant will have sufficient medical resources to assist the mother. [ 17 , 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study in Malawi identified factors such as illiteracy, unemployment, and lack of social support to be significantly associated with higher levels of fear ( 2 ). These inconsistencies may be attributed to differences in sample characteristics, cultural factors, or measurement instruments used to assess childbirth fear ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%